PENGARUH MULTIMEDIA NCESOFT FLIPBOOK MAKER PADA MATERI PEMBELAJARAN PENGENDALIAN GULMA TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA KELAS XI ATPH SMK NEGERI 1 BONE-BONE - Istigfar, Andi Muhammad; Wijaya, Mohammad; Nurmila, Nurmila (Jurnal Pendidikan Teknologi Pertanian, 2018)
This research is Pre-experiment research which is aimed to know and analyze the influence of Ncesoft Flipbook Maker multimedia usage on motivation and student learning result of class XI ATPH SMK Negeri 1 Bone-Bone academic year 2017/2018 with total sample of 24 students implemented in the form of design One Group Pretest Posttest Design. Data collection techniques used in the research are observation techniques, questionnaires, documentation, interviews and tests. The data obtained was analyzed and processed using SPSS version 16. From the results of this study showed that the use of multimedia Ncesoft Flipbook Maker affect the motivation and student learning outcomes on weed controlling learning material in class XI ATPH SMK Negeri 1 Bone-Bone. this can be seen from the magnitude of the influence of learning motivation generated multimedia of 17.00%. The result of coefficient test known tcount value of 2,124 with significance value 0.045 <0.05 and the magnitude of multimedia influence on learning outcome of 21.50%. The result of coefficient test known tcount of 4,378 with significance value 0.000 <0.05.